O Ano Litúrgico como itinerário teológico e pedagógico da fé - Ferreira, Eurivaldo Silva (2013)
In this paper we aim to show the Liturgical Year as an educational journey of faith. The reform of Second Vatican Council considered the liturgy as living the faith, the example of the first christian communities. From Sacrosanctum Concilium, the Liturgical Year is organized to contribute to the spiritual transformation of the faithful. Starting time sensitive signal underlying pedagogy of the Liturgical Year, we sought to clarify his theological virtue, since, through him, they remember the mysteries present in the Liturgical Year. During the literature review sought to explore the theology of the Liturgical Year and their implications in the context of liturgical reform. We identified as key participation as primary substrate of faith, and propose methodological suggestions so that participation can be contemplated in the mysteries that the Liturgical Year presents and have resonance in the concrete life of faith communities